(untitled) - Quinn, Lori (United States, 2003)
This hands-on textbook/workbook teaches readers how to document functional outcomes in a clear, logical progression. Extensive examples and exercises in each chapter highlight the essential points of functional outcomes documentation, designed to help improve client function and reduce disability as well as provide evidence of functional progress for insurance payment and reimbursement.
Keywords: Physical therapy,Physical therapy assistants,Vật lý trị liệu,Phụ tá vật lý trị liệu